1997
DOI: 10.1007/pl00004982
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of protein kinase C is involved in the inhibition by cycloheterophyllin of neutrophil superoxide anion generation

Abstract: Cycloheterophyllin, a prenylflavone, inhibited the superoxide anion (O2-) generation from formylmethionyl-leucyl-phenylalanine (fMLP)- and phorbol 12-myristate 13-acetate (PMA)-stimulated rat neutrophils in a concentration-dependent manner with IC50 values of 47.0 +/- 5.0 and 1.7 +/- 0.4 microM, respectively. Cycloheterophyllin had no effect on O2- generation in xanthine-xanthine oxidase system and during dihydroxyfumaric acid (DHF) autoxidation. Cycloheterophyllin exerted a concentration-dependent inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…To evaluate this possibility, HEK293 cells were treated with PMA (phorbol 12-myristate 13-acetate) (500 nM; 60 min) to then assess changes in ligand-induced βarr2 recruitment and internalization. Activation of typical and novel PKC isoforms by the phorbol ester [42, 43] increased βarr2 recruitment (Fig. 6a) and DOR internalization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this possibility, HEK293 cells were treated with PMA (phorbol 12-myristate 13-acetate) (500 nM; 60 min) to then assess changes in ligand-induced βarr2 recruitment and internalization. Activation of typical and novel PKC isoforms by the phorbol ester [42, 43] increased βarr2 recruitment (Fig. 6a) and DOR internalization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…heterophyllus . Previous studies have reported that cycloheterophyllin has anti-platelet, anti-oxidative, anti-inflammatory, anti-diabetic, and anti-tuberculosis activity [911, 23, 24]. In this study, we further investigated the molecular mechanisms and biological activities of cycloheterophyllin with a particular focus on its protective effect against UVA-induced damage and oxidative stress injury.…”
Section: Discussionmentioning
confidence: 98%
“…Cycloheterophyllin (C 30 H 30 O 7 ), a prenylflavone (Fig 1A), is isolated from Artocarpus heterophyllus , and has pharmacological and biological functions including anti-inflammatory effects, anti-platelet activities, and antioxidant properties [811]. However, it is unknown whether cycloheterophyllin can modulate the signaling pathways triggered by UVA in human dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils (4 × 10 7 cells ml −1 ) were stimulated with kazinol B or phorbol 12‐myristate 13‐acetate (PMA) at 37°C, and then disrupted in Tris buffer with 1 mM EGTA and 10 μg ml −1 of leupeptin and antipain by sonication, and fractionated as previously described (Wang et al , 1997b). The cytosol and the particulate fractions were stored at −70°C until use.…”
Section: Methodsmentioning
confidence: 99%